Relationship of Serum Prostate Specific Antigen with Hirsutism in Women Having Polycystic Ovary Syndrome Belonging to the Province of Khyber Pakhtunkhwa, Pakistan - Khattak, Naheed; Durrani, Sadaf; Ali, Sobia; Tariq, Kalsoom; ur Rahman, Ubaid; Khan, Mudassir Ahmad (Journal of Liaquat University of Medical & Health Sciences, 2023)
Objective: To find the relationship of serum PSA with Hirsutism in PCOS females of Khyber Pakhtunkhwa. Methodology: It was a cross-sectional/comparative study. This study was conducted in Khyber Teaching Hospital, Lady Reading Hospital, and Hayatabad Medical Complex from June to December 2021. A total of 172 study subjects were involved in this study. Serum PSA, testosterone and DHEAS levels of 86 newly diagnosed cases of PCOS (Group A) were compared with 86 healthy age-matched controls (Group B). These parameters were estimated using the ELISA method. Distribution of Hirsutism of the study subjects was also established with FGS. SPSS version 21 was used to analyze the data. Results: The results showed that serum PSA significantly increased (0.325±0.243 Vs 0.119±0.209, P <0.0001) in females with PCOS. Serum total testosterone (1.639±0.773 vs 0.739±0.965, P<0.0001) and DHEAS (3.397±1.243 Vs 2.035±1.203, P <0.0001) levels were also raised. A highly significant positive relationship was seen between PSA with Hirsutism through FGS (r 0-609, P 0.000), testosterone (r 0.352, P 0.000) and DHEAS levels (r 0.432, P 0.000) Conclusion: This study observed significantly high PSA correlating positively with Hirsutism in females with PCOS. Keywords: Prostate Specific Antigen, Hirsutism, Polycystic Ovary Syndrome